The Manasik of Hajj in Indonesia: Looking for Legal Certainty through the Reasonings of Usul al-Fiqh - Nasrullah, Nasrullah (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2020)
The paper aims to seek legal certainty of the manÄsik in Indonesia from the perspective of uá¹£Å«l al-fiqh. In the classical fiqh, the manÄsik has not received proper attention. Hence, the legal position of manÄsik has thus far no definite (qaá¹Ê¿Ä«) answer. For today's Indonesia, although the manÄsik is understood more as training for prospective pilgrims on how to perform the á¸¥ajj correctly, yet it is different from what the Prophet Muhammad practiced, which was conducted directly within the á¸¥ajj rituals. With that aim in mind, this paper uses the reasoning devices of uá¹£Å«l al-fiqh such as bayÄnÄ«, taâ€˜lÄ«lÄ«, and istiá¹£lÄhÄ« toward the relevant literary sources in establishing a legal certainty of the manÄsik. The bayÄnÄ« method shows that the texts of the prophetic traditions contain imperative expression (amr), meaning that the manÄsik is an obligatory practice. The taÊ¿lÄ«lÄ« points out that the manÄsik stands as Ê¿illa for the perfection of á¸¥ajj; the manÄsik is necessary to make á¸¥ajj ritual ideally conducted. The istiá¹£lÄá¸¥Ä« method reveals that the manÄsik contains the value of maá¹£laá¸¥a, which is the validity of á¸¥ajj based on sharia principles. Finally, from the perspective of maqÄá¹£id al-sharÄ«Ê¿a, the necessity of the manÄsik is classified into á¸arÅ«riyya and á¸¥Äjiya. Hence, based on these arguments, this paper argues that the manÄsik of á¸¥ajj is obligatory for prospective pilgrims.